(untitled) (Palimpsesto, 2026)
Feminized aging places many older women in precarious situations and loneliness. From a feminist and participatory approach, through semi-structured group interviews and the collective creation of a cyanotype, this study explores the meanings that a group of older women in Valparaíso (Chile) attribute to their daily practices of mutual care. Content analysis identified three dimensions of this: material, affective, and symbolic. The conclusion is that mutual care articulates concrete actions, emotional bonds, and shared meanings; it generates support networks to address inequalities and constitutes a form of dignifying and empowering collective action offering alternatives to the hegemonic model of care.